Self-assembled manganese dioxide nanowires as electrode materials for electrochemical capacitors - Chin, Suk Fun; Pang, Suh Cem; Anderson, Marc A. (Elsevier B.V, 2010)
The microstructure and morphology of sol–gel derived manganese dioxide (MnO2) xerogels were affected by the synthesis conditions and post synthesis heat treatment. Manganese dioxide nanoparticles in sol that were dialyzed to more acidic pH (pH 5.7) value were observed to self-assemble into nanowires, whereas nondialyzed sols remained nanoparticulate in nature. MnO2 xerogels of disordered nanowire network exhibited comparatively higher porosity and BET surface areas. The electrochemical properties of both MnO2 nanowire and nanoparticle thin-film electrodes were evaluated using cyclic voltammetry in a mild aqueous electrolyte (0.1 MNa2SO4). The charge capacities of MnO2 nanowire-based thin-film electrodes were substantially higher (~800 F/g) than those of nanoparticulate thin-film electrodes (~700 F/g).